2017
DOI: 10.1016/j.knee.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Angioleiomyoma in the posterior knee: A case report and literature review

Abstract: The authors present a case of angioleiomyoma situated in the posterior knee. A 47-year-old Caucasian woman presented in 2011 with recurrent stabbing pain on the lateral aspect of her right knee. She reported having pain for the last 6years. She had no history of trauma. In 2008 she was treated with a diagnostic arthroscopy and transposition of the tibial tuberosity, with no benefit to her symptoms. Electromyography of the lower limbs showed asymmetry of the amplitude of sensitive action potential of the superf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Angioleiomyomas and lipoleiomyomas in the inguinal canal are rarely reported, and the swelling and presenting symptoms of our patients were initially attributed to an inguinal hernia. Distinguishing a lipoma in the canal of Nuck from an inguinal hernia is not easy using ultrasonography because they both show a homogenous structure with a well-defined margin [7]. Avritscher et al [8] suggested that the tumor may arise from misplaced embryonic remains of lipoblasts or due to the perivascular extension of peritoneal or retroperitoneal fat.…”
Section: Discussionmentioning
confidence: 99%
“…Angioleiomyomas and lipoleiomyomas in the inguinal canal are rarely reported, and the swelling and presenting symptoms of our patients were initially attributed to an inguinal hernia. Distinguishing a lipoma in the canal of Nuck from an inguinal hernia is not easy using ultrasonography because they both show a homogenous structure with a well-defined margin [7]. Avritscher et al [8] suggested that the tumor may arise from misplaced embryonic remains of lipoblasts or due to the perivascular extension of peritoneal or retroperitoneal fat.…”
Section: Discussionmentioning
confidence: 99%
“…Allerdings sind die Schmerzen sehr unterschiedlich ausgeprägt, oft nur nach Irritationen (Tuberculum dolorosum). Aber der Schmerz kann auch konstant auftreten, paroxysmal, scharf-stechend oder getriggert (Druck, Östrogene, Kälte u. a) [5]. Auch die Genese der Schmerzen ist unklar.…”
Section: Kommentarunclassified
“…Angiomyomas similarly involve nerves of the lower extremities and have been reported in the sciatic nerve [ 12 ]. By and large, angiomyomas have a predilection for affecting females in the lower extremities [ 13 ], and in particular, involving the knee [ 14 - 15 ]. Involvement in the plantar aspect of the heel has also been described [ 16 ].…”
Section: Introductionmentioning
confidence: 99%